Review on HIV among women in nursing perspective - Mardiana, Mansor (2017)
The article review was to identify, discuss, explore, critically analyze and evaluate the scenario of Human ImmunodeficiencyVirus (HIV) among women in nursing perspective taking into account global perspective. The current aim is to reduce the number of HIV globally, especially among women. Acquired immune deficiency syndrome (AIDS) is considered as a disease state of hopelessness and imminent death. HIV and AIDS status demotivate the women emotionally in physical, social, and emotional perspectives. HIV-positive women portray of AIDS is deeply discrediting; with physical failure, moral failure, and social ostracism.